Overlap SJS-TEN in a kid and management protocols - Sonali Mukherjee; Bikramjit Barkondaj; Chandan Chatterjee (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2020)
Toxic Epidermal Necrolysis (TEN) and Steven Johnson Syndrome (SJS) are usually of drug-related reasons and infectious etiology. This is often defined by detachment of cuticle and lysis. SJS-TEN OVERLAP is TEN and SJS like syndrome characterized by involvement of more than 10% body surface area. But it is limited within 30%. Different types of purpuric macules or rounded patches with mucosal lesions are the characteristic features of this type 3 hypersensitivity reaction. SJS/TEN overlap uninterruptedly presented with fever for 2-3 days. It may be associated with anorexia and malaise., Sometimes, associated with pharyngitis extending an additional few days. Mucosal lesions appeared early. Later it is followed by skin lesions. Most commonly oral mucosa, genitalia, and conjunctiva are involved at the beginning. Two out are three are commonly involved. In our case, we are presenting a boy of 4 years old suffering from SJS-TEN overlap recovered completely after stopping the sinning drug and treatment with Immunoglobulin with other symptomatic measures. The culprit was found to be Amoxicillin and medicine dispensed by his parents without taking consultation with the clinician.